Ectopic Expression of JcWRKY Transcription Factor Confers Salinity Tolerance via Salicylic Acid Signaling - Agarwal, Parinita; Dabi, Mitali; Sapara, Komal K.; Joshi, Priyanka S.; Agarwal, Pradeep K. (Frontiers in Plant Science, 2016)
Plants, being sessile, have developed intricate signaling network to specifically respond to the diverse environmental stress. The plant-specific WRKY TFs form one of the largest TF family and are involved in diverse plant processes, involving growth, development and stress signaling through auto and cross regulation with different genes and TFs. Here, we report the functional characterization of a salicylic acid -inducible JcWRKY TF. The JcWRKY overexpression confers salinity tolerance in transgenic tobacco, as was evident by increased chlorophyll content and seed germination potential. The transgenic plants showed increased soluble sugar, membrane stability, reduced electrolyte leakage and generation of reactive oxygen species (H2O2 and O2•-) as compared to the wild type. Furthermore, the low SA treatment along with salinity improved the tolerance potential of the transgenics by maintaining ROS homeostasis and high K+/Na+ ratio. The transcript expression of SA biosynthetic gene ICS1 and antioxidative enzymes (CAT and SOD) showed upregulation during stress. Thus, the present study reflects that JcWRKY is working in co-ordination with SA signaling to orchestrate the different biochemical and molecular pathways to maneuvre salt stress tolerance of the transgenic plants.